Pengaruh Aplikasi Tik Tok dan Shopee Terhadap Minat Beli Kosmetik pada Mahasiswi Program Studi Pendidikan Tata Rias dan Kecantikan - Tiara Annisa; Dira Kusuma; Siska Miga Dewi (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
TikTok and Shopee are popular applications influencing cosmetic purchasing decisions among young individuals. This study examines their impact on cosmetic purchasing behavior among students in the Beauty and Cosmetic Education program. The objective is to objectively understand the influence of TikTok and Shopee on cosmetic purchasing decisions. A quantitative survey method was employed, targeting students from the 2021 and 2022 cohorts. Results indicate a significant impact of TikTok and Shopee on cosmetic purchasing behavior. Sampling utilized total sampling, with questionnaires as data collection instruments. Statistical analysis tested hypotheses regarding TikTok and Shopee's influence on purchasing decisions. Findings confirm significant effects on cosmetic purchasing. This research implies significant implications for understanding TikTok and Shopee's influence on cosmetic purchasing among Beauty and Cosmetic Education students.